The Influence Of Brand Image, Taste, And Price Perception On Purchasing Decisions For Sarimi Instant Noodles In Surabaya - Permata ELG Purba; Hery Pudjoprastyono (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Sarimi is a brand of instant noodles in Indonesia produced by Indofood CBP Sukses Makmur which was launched in 1982. Just like other instant noodle products, sarimi is sold in various types of products and flavors according to consumer needs. With so many brands of instant noodles in Indonesia, the reality is that sales of Sarimi instant noodles have decreased from year to year. This research aims to determine the influence of brand image, taste and price perception on purchasing decisions for sarimi instant noodles. The population of this study were Active Students of UPN "Veteran" East Java who had purchased and consumed sarimi instant noodles in Surabaya. This research used a quantitative method with 80 respondents collected using purposive sampling, namely, the sampling technique was determined using special or specific criteria for the sample. Meanwhile, the analysis used was Partial Least Square (PLS). The research results show that brand image, taste and price perception have a positive and significant effect on purchasing decisions for sarimi instant noodles.